Effect of hydrogen peroxide on thawed ovine sperm motility - Maia, M. S. (2014)
Oxidative stress, resulting from excessive levels of ROS in semen, has a negative impact on functional parameters and sperm fertility. In this study we examined the influence of the oxidative stress induced by hydrogen peroxide (H2O2) in ovine sperm motility after thawing and catalase (CAT) ability to preserve sperm motility. Semen was incubated at 37°C with 100 μM H2O2, 1 U catalase + 100 μM H2O2 or no treatment, for 30 min. Immediately after adding treatments, sperm motility was determined by computer-assisted semen analysis (CASA). Incubation with H2O2 led to a significant (P < 0.05) decrease in motility parameters whereas catalase prevented a decline in motility secondary to oxidative stress. After 30 min of incubation with H2O2, total motility (12.0% vs. control 73.0%, H2O2 +CAT 70.0%), progressive motility (0.0% vs. control 19.0%, H2O2 +CAT 19.0%) and rapid motility (1.0% vs. control 43.0%, H2O2 +CAT 40.0%) decreased significantly (P < 0.05), whereas percentage of static cells increased (84.0% vs. control 18.0%, H2O2 +CAT 20.0%). We conclude that H2O2 causes damage to ovine sperm motility and that catalase is able to avoid detrimental effect of H2O2 on sperm motility.